Understanding the Drivers of College Students’ Attitudes and Intentions Towards Online Shopping in China - Mao, Yi (Scholar: Human Sciences, 2025)
Purpose: This study aims to explore the factors that influence the purchase intention of online shopping among college students in Zhanjiang, China. The conceptual framework comprises subjective norm, trust in online shopping, convenience of online shopping, customer service offered by online shopping, value motive, attitude, and purchase intentions. Research design, data, and methodology: The sample data was collected using a quantitative method and a questionnaire as a tool. Before distribution, the questionnaire’s content validity and reliability were tested using Item-Objective Congruence and a pilot test. The data was then analyzed using Confirmatory Factor Analysis and Structural Equation Modelling to validate the model’s goodness of fit and confirm the causal relationship among variables for hypothesis testing. Results: The conceptual model effectively predicted purchase intention (PI) for online shopping among college students. Two key prerequisites for BI are attitude and value motive. Conclusions: ATT was the strongest predictor of PI to use both directly and indirectly, which ATT was driven significantly by subjective norm, trust in online shopping, the convenience of online shopping (COS), and customer service offered by online shopping (CSOS). Therefore, this study suggests that online purchasing platforms and merchants should improve the attitudinal factor of purchase intention so that students will find the system useful and develop a good attitude and purchase intention towards online shopping.